Editorial: The Remasculinization of Global Politics in the Contemporary Era - Dias Pabyantara Swandita Mahayasa (JUSS (Jurnal Sosial Soedirman), 2025)
Editorial: The Remasculinization of Global Politics in the Contemporary Era